Comparison of Different Risk Assessment Tools to Manage Musculoskeletal Disorders Among Workers in an Automobile Manufacturing Company - Jafarian, Mohadeseh; Hoseini, Nesa; Safahieh, Amirhossein; Namnabat, Mohammad Sadegh; Arjmand, Navid (2023 30th National and 8th International Iranian Conference on Biomedical Engineering (ICBME), 2023)
Awkward postures and manual material handling activities are important risk factors for musculoskeletal disorders in workers. To avoid the harm and costs caused by these injuries, there are several ergonomics (e.g., MAC, ManTRA, NIOSH, OWAS, QEC, REBA, WISHA, Snook, and V3) and biomechanical (i.e., biomechanical models such as AnyBody Modeling System, Jack, Regression equations, HCBCF and 3DSSPP) risk assessment tools. This study is conducted to compare these tools to evaluate working conditions in the cylinder finishing unit of Malleable Saipa Company as well as to suggest interventions to reduce the risk of injury. Results indicate that our case study work situation has a high risk of musculoskeletal injuries due to the cylinder's heavy weight and workers' improper posture; therefore, job interventions are required. The recommended interventions, including load height adjustment, worker training, job rotation, and team working significantly reduced the risk of injury. Comparisons between the risk assessment tools indicate that QEC, ManTRA, and V3 tools are more comprehensive than other ergonomics tools. Moreover, all methods show compression more than 50% higher than AnyBody which is the most accurate method. The fact that the load's weight (36 kg) exceeded the maximum permissible load for these tools (20 kg) is probably what caused this issue.